Do debate à implementação: a versão não oficial da adoção das cotas raciais na UFPB. - Costa, Nayara Tatianna Santos da (2012)
The need to understand how they processed the construction of the quota politics at the Federal University of Paraíba, in concerns to the quotas for blacks in particular and beyond what is expressed in official documents, originated this dissertation. In this sense, the study proposed to reveal the approach of a history from below, as the themes was discussed in the interstitium of 2007-2010 by the academy, which arguments were defended by teachers engaged in initial discussions on the implementation of quotas with part racial and positioned themselves as representatives of social movements involved in the construction of this politics in UFPB. To this end, the research focused three times: Bibliographic research, documents research, in the archives of UFPB, linked to CONSEPE, the CONSUNI and PRG, and the Laws 10.639/2003 and 11.645/2008, the recommendation of the MPF and documentary; field research with teachers engaged in the discussion Home on the implementation of racial quotas with, using a semi-structured interviews. Based on Munanga (2008), Aragon Et. Al (2008), Aquino (2011), Fonseca and Rocha (2010) Burke (1992) and Hobsbawm (1998), among others, the data analysis was done in a predominantly qualitative and revealed, among other things, the approval quotas for the black population was influenced prevalent in UFPB Project UFPB-REUNI and the performance of federal prosecutors.